The association between frailty and satisfaction with social contacts in the general older population. (13th November 2019) - Nguyen, D; Braekman, E; Demarest, S; der Heyden, J Van
Abstract: Background: As a result of the demographic evolution, the proportion of older people will continue to increase in the coming decades. Frailty among elderly is one of the important challenges that Europe is facing. From a biomedical, perspective frailty is considered as a clinical syndrome that increases vulnerability. However, the role of social contacts in relation to frailty needs to be investigated. In this study, we assessed the association between frailty and perceived satisfaction with social contacts in a sample of the general older population. Methods: This study was conducted on a representative sample of 2364, both institutionalized and non-institutionalized older participants (≥65 years) from the Belgian Health Interview Survey 2018. Frailty was assessed with the instrument used in the Survey of Health Ageing and Retirement in Europe (SHARE) including dimensions of the Fried phenotype: exhaustion, weight loss, muscle strength, weakness and physical activity. The Oslo-3 Social Support Scale (OSS-3) was used to assess perceived quality of social support. Logistic regression was used to determine the association between frailty status and satisfaction with social contacts while controlling for age, gender, region, educational attainment and household composition. Results: The prevalence of frailty was 22.8% (95%CI:21.2-24.6). The results showed that elderly who are unsatisfied with their social contacts are more likely to be frail (OR(95%CI):4.65 (2.82-7.66)). In addition, being older ≥75 years (OR(95%CI):2.40 (1.68-3.43)), being female (OR(95%CI):2.48 (1.73-3.56)), having a lower education (OR(95%CI):2.57 (1.71-3.87)), living alone (OR(95%CI):1.58 (1.10-2.27)) were associated with frailty. Conclusions: Frailty is associated with living alone and being unsatisfied with the social contacts, among older people in Belgium. These findings confirm that the social component should be taken into account in strategies to reduce frailty in the general older population. Key messages: Frailty is associated with living alone and being unsatisfied with the social contacts, among older people in Belgium. The social component should be taken into account in strategies to reduce frailty in the general older population.